2012
DOI: 10.1371/journal.pone.0030958
|View full text |Cite
|
Sign up to set email alerts
|

The Nitric Oxide-Cyclic GMP Pathway Regulates FoxO and Alters Dopaminergic Neuron Survival in Drosophila

Abstract: Activation of the forkhead box transcription factor FoxO is suggested to be involved in dopaminergic (DA) neurodegeneration in a Drosophila model of Parkinson's disease (PD), in which a PD gene product LRRK2 activates FoxO through phosphorylation. In the current study that combines Drosophila genetics and biochemical analysis, we show that cyclic guanosine monophosphate (cGMP)-dependent kinase II (cGKII) also phosphorylates FoxO at the same residue as LRRK2, and Drosophila orthologues of cGKII and LRRK2, DG2/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Without knowing the precise tissues or cells where foraging expression is required to alter its associated behaviors, it is difficult to speculate on the nature of the gene networks in which it resides. That being said, previous genetic evidence has suggested possible interaction with insulin-signaling and foxo-signaling (Kent et al 2009;Kanao et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Without knowing the precise tissues or cells where foraging expression is required to alter its associated behaviors, it is difficult to speculate on the nature of the gene networks in which it resides. That being said, previous genetic evidence has suggested possible interaction with insulin-signaling and foxo-signaling (Kent et al 2009;Kanao et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The Foxo-induced phenotype of developmental defects in the Drosophila eye is likely due to the transcription of pro-apoptotic gene targets. Drosophila studies link phosphorylation of Foxo to neurodegeneration, and have identified the pro-apoptotic Hid gene as one responsible target, where overexpression of Hid causes dramatic eye degeneration [29,30,37]. In contrast, Foxo has also been shown to prevent mitochondrial dysfunction and neurodegeneration, and is proposed to function downstream of Pink1 [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genes that promote stress resistance, under conditions of oxidative stress or starvation, Foxo transcription factors may also target genes that promote cell cycle arrest and apoptosis [27,28]. Overexprssion of Foxo has been linked to neurotoxicity [29,30] and overexpression in the developing Drosophila eye results in a characteristic phenotype with reductions in cell number and area [31]. Genetic expression studies using the fly eye have been enormously successful in the study of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that, among the myriad processes and factors involved, oxidative stress and NO have a key role in neurodegenerative processes suggests that they could be potential targets of novel therapeutic strategies (Foley and Riederer, 2000;Džoljić et al, 2005) New results, more precisely, show signaling pathways underpinning synapse loss in PD. Paracrine/retrograde NO action activates the soluble guanylyl cyclase/PKG pathway and RhoA/Rho kinase (ROCK) signaling resulting in loss of synapses (Kanao et al, 2012). In addition, NO, through the cGMP pathway, regulates the activity of transcriptional factor FoxO and alters dopaminergic neuron survival, potentiating its neurotoxicity (Kanao et al, 2012).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Paracrine/retrograde NO action activates the soluble guanylyl cyclase/PKG pathway and RhoA/Rho kinase (ROCK) signaling resulting in loss of synapses (Kanao et al, 2012). In addition, NO, through the cGMP pathway, regulates the activity of transcriptional factor FoxO and alters dopaminergic neuron survival, potentiating its neurotoxicity (Kanao et al, 2012). Moehle et al (2012) revealed the role of iNOS-derived NO in PD neurodegeneration, showing effects of microglial secretion of iNOS-derived NO on leucine-rich repeat kinase 2 (Moehle et al, 2012).…”
Section: Neurotoxicitymentioning
confidence: 99%